The cell cycle of Staphylococcus aureus: An updated review. Issue 1 (9th December 2022) - Barbuti, Maria D.; Myrbråten, Ine S.; Morales Angeles, Danae; Kjos, Morten
Abstract: As bacteria proliferate, DNA replication, chromosome segregation, cell wall synthesis, and cytokinesis occur concomitantly and need to be tightly regulated and coordinated. Although these cell cycle processes have been studied for decades, several mechanisms remain elusive, specifically in coccus‐shaped cells such as Staphylococcus aureus . In recent years, major progress has been made in our understanding of how staphylococci divide, including new, fundamental insights into the mechanisms of cell wall synthesis and division site selection. Furthermore, several novel proteins and mechanisms involved in the regulation of replication initiation or progression of the cell cycle have been identified and partially characterized. In this review, we will summarize our current understanding of the cell cycle processes in the spheroid model bacterium S. aureus, with a focus on recent advances in the understanding of how these processes are regulated. Abstract : DNA replication, chromosome segregation, synthesis of the septal cell wall, and cytokinesis occur concomitantly in staphylococci. The processes are tightly coordinated temporally and spatially.